Pendampingan Usaha Mikro, Kecil dan Menengah (UMKM) Dalam Pemanfatan Digital Marketing Di lingkungan RT.03 / RW.02 Kelurahan Kauman Kota Mojokerto - Khasbulloh Huda; Harjo Lukito; Mohamad Johan Efendi; Eny Nuraeny; Fatma Nur Laila; Fitria Rahma Aprilia; Alvian Herdiansyah (Fakultas Teknik Universitas Cenderawasih, 2023)
Technological developments that are developing rapidly at this time can be one way to overcome the problem of marketing MSME products by selling online. However, there are still many MSEs who have not been able to optimize technological progress as a role in digital marketing. The purpose of this Community Service is to provide assistance in the use of social media as a means of promotional media. By adding promotions on social media, it is hoped that the products produced will be known to a wider public, and can increase income. With existing social media, both via Facebook, Whats App and also Instagram, it is hoped that it will add to the existing market share and expand its market share.